Cultural diversity in Finland - Pauliina Raento; Kai Husso (Fennia: International Journal of Geography, 2002)
The image of Finland as a culturally and ethnically homogeneous nation is erroneous. The country’s ‘old minorities’ include the Swedish-speakers, the indigenous Sami, and the Romani. Several smaller ethno-cultural and religious groups have resided in Finland since the nineteenth century. Increasing immigration is now further diversifying Finland. Many of the old and new minorities have clearly-defined regional hearths, as do many distinctive segments of the majority culture. This article provides an overview of Finland’s three largest minorities, religions, foodways, the new immigration, and the recent English-language sources available on these topics. The discussion emphasizes the new understanding of the country’s ethno-cultural make-up and political, legal, and social challenges that have followed the recent change.